Improving Tracheostomy Care in Resource-Limited Settings. (February 2020) - Sandler, Mykayla L.; Ayele, Nohamin; Ncogoza, Isaie; Blanchette, Susan; Munhall, Daphne S.; Marques, Brittanie; Nuss, Roger C.
Objectives: Tracheostomy care in leading pediatric hospitals is both multidisciplinary and comprehensive, including generalized care protocols and thorough family training programs. This level of care is more difficult in resource-limited settings lacking developed healthcare infrastructure and tracheostomy education among nursing and resident staff. The objective of this study was to improve pediatric tracheostomy care in resource-limited settings. Methods: In collaboration with a team of otolaryngologists, respiratory therapists, tracheostomy nurses, medical illustrators, and global health educators, image-based tracheostomy education materials and low-cost tracheostomy care kits were developed for use in resource-limited settings. In addition, a pilot study was conducted, implementing the image-based tracheostomy pamphlet, manual suctioning device and low-cost ambulatory supply kit ("Go-Bags"), within a low-fidelity simulated training course for nurses and residents in Kigali, Rwanda. Results: An image-based language and literacy-independent tracheostomy care manual was created and published on OPENPediatrics, an open-access online database of clinician-reviewed learning content. Participants of the training program pilot study reported the course to be of high educational and practical value, and described improved confidence in their ability to perform tracheostomy care procedures. Conclusions: Outpatient tracheostomy care may be improved upon by implementing image-based tracheostomy care manuals, locally-sourced tracheostomy care kits, and tailored educational material into a low-fidelity simulated tracheostomy care course. These materials were effective in improving technical skills and confidence among nurses and residents. These tools are expected to improve knowledge and skills with outpatient tracheostomy care, and ultimately, to reduce tracheostomy-related complications.